DEVELOPMENT OF A RESEARCH SELF-EFFICACY SCALE: PRELIMINARY EVIDENCE OF VALIDITY - Dominguez-Lara, Sergio Alexis (2017)
The aim of this study was to examine the preliminary evidence of validity of the Research Self-Efficacy Scale (RSE) through the analysis of item contents. A sample of ten research psychologists (70% male; Mage = 47.2 years old), and 34 Peruvian college students (> 70% female), both undergraduate (n = 19) and graduate (n = 15) was assessed. The researchers evaluated the relevance and clarity of the items, and the students, the clarity of the RSE statements. The answers given by the judges were systematized through Aiken’s V with confidence intervals, obtaining favorable results. In conclusion, the RSE exhibits favorable evidence regarding the representativity of the items. The practical implications of the findings are discussed here.